The predictive value of the proportion of the contribution of some anthropometric measurements and the speed of the kinematic response to the performance of the wall skill in volleyball - Jabar , M.M Sura Sattar; Muhammad , Ameer Jassim; Muhammad , Ameer Jassim; Laibi , Mustafa Abdel Karim; Rahman , Mustafa Abdel (International Journal of Psychosocial Rehabilitation, 2020)
The problem of this study came in the lack of scientific research that dealt with the skill performance in relation to physical measurements and the speed of the movement response and knowledge of the extent of the impact of those variables on the skill performance, and given the importance of these variables in the performance of the defensive wall skill and their important role in being a defensive offensive skill. Delve into this phenomenon, and the problem crystallized by saying that the nature and speed of performance of the wall skill requires physical characteristics and special physical capabilities, and this can be observed through the results reflected in the performance of that skill, so the researchers decided to know the extent to which these variables contribute to the performance of the wall skill Blocking and predicting it, which will be an evidence of the benefit in raising a high mathematical level, while the study aimed to find predictive values of the blocking wall skill in terms of some physical measurements and the speed of the kinematic response and to identify the percentage of the contribution of those variables to the performance of that skill. The researchers concluded that the physical measurements and the speed of the movement response It contributed statistically significant percentages to the performance of that skill, as well as a predictive equation was devised through which the skill of the blocking wall could be predicted in terms of the most important measures. Physicality and speed of movement response and the researchers recommended the necessity of the coaches' attention when selecting players, taking into account the physical specifications, which are among the most important requirements of this sport, and the necessity of conducting tests for motor abilities and regarding the speed of response and its role is fundamental and influential in the performance of that event.